2015
DOI: 10.1007/s10695-015-0133-y
|View full text |Cite
|
Sign up to set email alerts
|

Deficient and excess dietary selenium levels affect growth performance, blood cells apoptosis and liver HSP70 expression in juvenile yellow catfish Pelteobagrus fulvidraco

Abstract: We investigated the effects of deficient and excess dietary selenium (Se) on growth, blood cells apoptosis and liver heat shock protein 70 (HSP70) expression in juvenile yellow catfish (Pelteobagrus fulvidraco). After 8 weeks, yellow catfish (initial weight: 2.12 ± 0.01 g) fed isonitrogenous and isolipid diets containing <0.05 (deficient dietary Se) or 6.5 (excess dietary Se) mg Se/kg displayed a significantly lower weight gain ratio (WGR) than those fed a diet containing 0.23 (normal dietary Se) mg Se/kg. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 80 publications
1
15
0
1
Order By: Relevance
“…Excessive Se (1.14 and 2.28 mg/kg) aggravated liver damage compared with the Cr(VI) treatment alone, Hu et al . and Xu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive Se (1.14 and 2.28 mg/kg) aggravated liver damage compared with the Cr(VI) treatment alone, Hu et al . and Xu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Normally, dietary selenium level had no effect on survival in fish (Hu et al, ; Liu et al, ). However, uses of plant‐based or low‐vitamin E diet in Atlantic salmon may allow selenium intake leading to immune‐promoting effect and improved survival rate (Berntssen et al, ; Thorarinsson, Landolt, Elliott, Pascho, & Hardy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Selenium is one of the trace elements known as an essential micronutrient for various biological and physiological functions in human and animals, including fish (Hamilton, 2004). Some studies showed that Se deficiency in fish caused growth depression, muscular lesion (Ilham & Fotedar, 2016), oxidative stress, loss of appetite, peroxidative damage and even death (Felton, Landolt, Grace, & Palmisano, 1996;Hu et al, 2016;Poston & Combs, 1979). However, excess amounts of Se may lead to haematological changes (Liu et al, 2018), poor feed efficiency (Pacini et al, 2012), deformities (Lemly, 1993) or toxicity to increase risk of mortality (Hilton, Hodson, & Slinger, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Krohn et al also found that moderate dietary selenium (from lentil) supplementation (>0.16 mg/kg) is associated with antioxidant defense against arsenic-induced hepatic oxidative stress in mice [ 19 ]. It has also been reported that either deficient or excessive dietary selenium (sodium selenite) cause oxidative stress in the liver of the juvenile yellow catfish Tachysurus fulvidraco [ 20 ]. Therefore, adequate dietary selenium was required for the maintenance of antioxidant enzyme system and helped to prevent hepatic mitochondria oxidative stress.…”
Section: Discussionmentioning
confidence: 99%